The UN International criminal tribunals: the former Yugoslavia, Rwanda and Sierra Leone - Schabas, William (Cambridge Univ. Press, 2006)
Creation of the tribunals -- The legitimacy and legality of the tribunals -- Sources of law --Territorial, personal and temporal jurisdiction -- Subject-matter jurisdiction generally -- Genocide -- Crimes against humanity -- War crimes -- General principles of law -- Investigation and pre-trial procedure -- Trial and post-trial procedure -- Evidence -- Rights of the accused -- Punishment -- Structure and administration of the tribunals